Assessing internal job candidates - Phillips, Jean, 1969- (Staffing strategically series., 2009)
Companies can find and explore different methods for evaluating current employees in this thorough and systematic guide. Discussing the primary goals of internal assessment--such as determining candidates for training, reassignment, promotion, or dismissal; deciding what developmental projects to assign employees; or effectively establishing who to dismiss and who to work hard to retain during downsizing--this manual relates the importance of this critical staffing function that many employees often do very poorly.